Geospatial analysis in managing medical facilities for combating disaster triggered by the COVID-19 pandemic - Usman F.; Hamim S.A.; Gumano H.N.; Jamil F. (IOP Publishing Ltd, 2023)
Viruses; Geo-spatial analysis; Geo-spatial data; Infectious disease; Local parameters; Medical facility; Monitoring purpose; World Health Organization; Wuhan , China; Disasters